2009
DOI: 10.1055/s-0029-1185539
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Diet-Induced Hypercholesterolemia by Scutellarin in Rats

Abstract: Hypercholesterolemia is a major risk factor for the development and progression of cardiovascular diseases including atherosclerosis. A major active ingredient scutellarin, from the plant Erigeron breviscapus was investigated for its hypocholesterolemic and atheroscleroprotective effects (30 and 100 mg/kg/day, p.o.). The serum lipid profile (total cholesterol, triglycerides, high density lipoprotein cholesterol and low density lipoprotein cholesterol) was monitored and aortic functions in Sprague-Dawley rats f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…In a recent report, breviscapine inhibited the proliferation and collagen production of cardiac fibroblasts that is induced by angiotensin II, as well as angiotensin II-induced phosphorylation of p38 and ERK1/2 MAPK [19] . Because the ERK1/2 MAPK pathway was activated in response to hyperglycemia and was involved in the high glucose-induced proliferation and migration of VSMCs, we tried to establish whether the MAPK pathway plays a role in the protective effect of breviscapine against VSMC functional impairment under high glucose conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent report, breviscapine inhibited the proliferation and collagen production of cardiac fibroblasts that is induced by angiotensin II, as well as angiotensin II-induced phosphorylation of p38 and ERK1/2 MAPK [19] . Because the ERK1/2 MAPK pathway was activated in response to hyperglycemia and was involved in the high glucose-induced proliferation and migration of VSMCs, we tried to establish whether the MAPK pathway plays a role in the protective effect of breviscapine against VSMC functional impairment under high glucose conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about whether breviscapine has a protective role in diabetic atherosclerosis, which is a common complication of diabetes mellitus that is independent of diabetic cardiomyopathy. A previous study demonstrated that breviscapine potentially had a protective effect on atherosclerosis and caused a significant reduction in the atherogenic index in rat atherosclerotic models [19] . However, whether breviscapine's anti-atherogenic effect resolves the functional impairments of VSMCs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 1 (control) was fed with normal rat chow, which was obtained from Lipton India Ltd [composition: protein (~14%), fat (~10%) and carbohydrate (~76%)]. Other groups of animals were fed with hypercholesterolemic diet (HCD) contained normal rat chow with the supplement of cholic acid (1%), cholesterol (2%) and cooking oil (5.5%) as described elsewhere (Yan et al, 2006;Li et al, 2009). Group 2 (model control) rats were treated orally with 10 ml/kg of 0.5% methylcellulose (w/v) in distilled water.…”
Section: Hypercholesterol Diet Induced Model Of Hyperlipideamiamentioning
confidence: 99%
“…Scutellarin has been extensively used for the clinical treatment of cardiovascular and cerebrovascular diseases in China for many years. Pharmacological research indicates that scutellarin is associated with antihypertrophic effects [1] , fibrinolysis and anticoagulant effects [2] , protective effects in the brain and heart [3] , hypercholesterolemia suppression [4] , and endothelium-independent relaxation induction [5] . Scutellarin produces an anti-inflammatory effect via actions on arachidonic acid metabolism [6] .…”
Section: Introductionmentioning
confidence: 99%